Peredaran Produk Makanan Tanpa Sertifikat Halal Dalam Perspektif Perlindungan Konsumen - Shintya Maulani Safira; Sutarman Yodo; Muhammad Ikbal; Agus Lanini; Erlan Ardiansyah (Jurnal Ilmu Hukum, 2026)
This article analyzes legal settlements related to food purchase transactions with a focus on the non fulfillment of consumer rights regarding the circulation of non-halal products on the market and the legal implications related to certification obligations. This study is conducted to determine forms of consumer protectio and legal implications related to the circulation of products on the market that do not yet have halal certification. This study uses an empirical juridical an approach that merges primary data gathered from structured interviews with secondary data obtained from relevant legal sources and literature. The results suggest that legal protection for consumers is not fully effective due to the presence of business actors who sell products without certainty about their halal status. To overcome this, preventive and repressive forms of protection can be implemented. The implementation of laws related to halal certification obligations is carried out through socialization, education, supervision, and strict law enforcement. This research contributes to the development of consumer protection discourse by emphasizing the importance of strengthening supervision and transparency related to halal certification.